Task Specificity of Dynamic Resistance Training and Its Transferability to Non-trained Isometric Muscle Strength: A Systematic Review with Meta-analysis - Saeterbakken, Atle H.; Stien, Nicolay; Paulsen, Gøran; Behm, David George; Andersen, Vidar; Solstad, Tom Erik Jorung; Prieske, Olaf (Sports medicine (Auckland), 2025)
Resistance training (RT) specificity has been confirmed for movement patterns (e.g., multi-joint or single joint), movement velocities, ranges of motion, and contraction types (e.g., dynamic vs isometric). However, a systematic analysis of the effects of dynamic mass-loaded (e.g., isoinertial) RT on dynamic versus isometric strength tests is lacking. We aimed to examine the specific effects of dynamic RT on dynamic (isoinertial) versus isometric muscle strength, including possible moderating factors (e.g., training length, single joint and multi-joint, upper body and lower body, RT status) and mechanisms (e.g., hypertrophy, muscle activation). A systematic literature search was conducted in MEDLINE (EBSCO), Web of Science, and Scopus up to March 2024. The included interventions contained at least ten training sessions, both dynamic and isometric muscle strength assessments before and after the training period, and healthy participants aged 16-60 years (encompassing untrained and trained individuals). Advanced RT approaches, such as electrical stimulation, isokinetic training, velocity-based training, and blood flow restriction training, were excluded. Within-subject, weighted standardized mean differences (SMDs) of the pre-intervention to post-intervention tests were calculated for both dynamic and isometric muscle strength measures using a random-effects model. Univariate sub-group analyses of RT status, intervention length, complexity (i.e., single-joint or multi-joint exercises), and body segments (i.e., upper and lower body) were independently computed. Random-effects meta-regressions were computed to examine if dynamic RT effects on dynamic and isometric muscle strength are predicted by RT effects on muscle hypertrophy or muscle activity. Overall, 43 studies with 1660 participants across 72 different RT interventions were eligible for inclusion. The overall effect on dynamic strength was significant and moderate magnitude (SMD = 0.98, 95% confidence interval 0.91-1.06, p < 0.001), whereas the transfer to non-trained isometric strength measures was significant but small (SMD = 0.42, 95% confidence interval 0.35-0.49, p < 0.001). Sub-analyses demonstrated moderate-to-large task-specific effects (range SMD; 95% confidence interval 0.75-1.30) of conducting dynamic RT and only small-to-medium effects (range SMD; 0.29-0.70) of the transferability of muscle strength to the non-trained isometric contraction form. Muscle hypertrophy and activity changes did not significantly predict dynamic RT effects on dynamic and isometric muscle strength (p ≥ 0.222). Our findings demonstrated task specificity of dynamic RT, as dynamic strength increased with a two-fold larger effect size than non-trained isometric muscle strength. Medium-to-large effects were observed for the dynamic strength improvements in the different sub-group analyses with small-to-medium effects in the isometric improvements. The limited transferability of dynamic (task-specific) strength to non-trained isometric contractions suggests that these two strength outcomes represent different neuromuscular domains.